A study on risk factors of abortion in a tertiary care hospital in Thrissur District, Kerala - Sunil, Vivek; Valsan, Sruthi Mankara (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Abortion is the spontaneous termination of pregnancy before 22 weeks or if the foetus weighs less than 500 gm. Spontaneous abortions may occur as a result of genetic factors, infectious agents, uterine abnormalities and other maternal factors. The present study was undertaken to study risk factors of abortion in a tertiary care hospital in Thrissur district. Methods: A hospital based case control study was done during a five month period. The sample size was calculated using the formulae [(Zα + Zβ)2 × 2 × PQ]/d2. Total 40 mothers admitted with abortion were taken as cases and 40 mothers admitted with conditions other than abortion of the same trimester were taken as controls. Data was collected with the help of an interviewer administered semi structured questionnaire. Results: Out of total 80 mothers, 46.2% of them belongs to 21-25 age group and more than half, 66.2% of the mothers were primi gravida. There was a statistically significant association between mother’s occupation and occurrence of abortion. The abortion rates were higher among overweight mothers, but this difference was not statistically significant. Among obstetric determinants, previous history of abortion, primi gravida mothers, and history of travel had higher risk for abortion with odds ratio 3.5, 2.8, and 2.72 respectively. Conclusions: Previous history of abortion and history of travel contributes to higher risk of abortion. Interventions could be targeted more on women with prevalent risk factors to increase health profits.